The Effects of Ethnoscience Integrated STEM E-Book Application on Student’s Science Generic Skills in Chemical Equilibrium Topic - Azalia, Izatul; Sudarmin, Sudarmin; Wisnuadi, Aries (International Journal of Active Learning, 2020)
This study aims to know the effects of the application of ethnoscience integrated STEM e-book on learning outcomes and student's science generic skills on chemical equilibrium topic. The research method that used is experiment and the research design that used is Pretest- posttest Control Group Experiment.Ã‚Â The sample of this research was taken by cluster random sampling technique, there are XI IPA 4 as an experimental class and XI IPA 3 as a control class. Data collection techniques are carried out with a reasonable multiple choice test to measure learning outcomes and student's science generic skills, questionnaires to find out students' responses to the e-book that used as teaching materials. Data analysis techniques that used is the average difference test, analysis of the effects between variables, and the stipulation of the determination coefficient. The research results obtained by the average cognitive learning outcomes of students in the experimental class and control class respectively 78.64 and 51.21. Analysis of the effects between variables shows a biserial coefficient is 0.90. Calculation of the determination coefficient shows the implementation of ethnoscience integrated STEM e-book accounted for 82%. While the average science generic skills of students in the experimental class and control class were 77.81 and 35.58, respectively. Analysis of the effects between variables shows a biserial coefficient is 0.97. Calculation of the determination coefficient shows that the application of ethnoscience integrated STEM e-book contributed 95%. Based on the results of the study it can be concluded that the application of ethnoscience integrated STEM e-book has an effect on learning outcomes and students' science generic skills in chemical equilibrium topic